Perjuangan Abdul Wahid VS Kolonial Belanda di Jambi (1916): Study Pengembangan Bahan Ajar Pembelajaran Sejarah: Indonesia - Reka Seprina; Yuliana Yuliana (Jurnal EduSosial, 2022)
This research was conducted to examine how Abdul Wahid's resistance against the Dutch Colonials that can be used as a teaching material in historical learning. This research method was conducted to examine how Abdul Wahid's resistance against the Dutch Colonials that can be used as a teaching material in historical learning. The research method used in the writing of this article is in the form of descriptive Qualitative methods. The results of this study showed that Abdul Wahid's struggle against the Dutch Colonial in Jambi that occurred in 1916 was one of the reactions of the Jambi people to the colonization carried out by the Dutch that brought misery to the people of Jambi. Abdul Wahid's struggle against the Dutch Colonial in Jambi can be used as a source of local history jambi and as a teaching material on historical learning for learners because this material is closely related to the environment they live in so as to make this historical learning more meaningful, can shape the personality of learners to love the homeland more, have a spirit of patriotism and increase nationalism and defend the country for The next generation of the nation.